Management and perinatal outcomes of hypertensive disorders of pregnancy in a low-resource setting in Indonesia - Kevin Dominique Tjandraprawira (SAGE Publishing, 2021)
Objectives: To provide up-to-date data concerning hypertensive disorders of pregnancy on maternal and neonatal profiles in Indonesia. Methods: Retrospective clinical audit on all pregnancy-associated hypertensive women between 1 January 2020 and 31 March 2020 at Cianjur General District Hospital. Results: Preeclampsia accounts for 66.8% (235/352) of hypertensive disorders of pregnancy, gestational hypertension 29% (102/352) and chronic hypertension 4.3% (15/352). Compared to other pregnant women, those with preeclampsia, on average, had higher systolic and diastolic blood pressures and poorer kidney (ureum and creatinine) and liver function (aspartate transaminase enzyme and alanine transaminase enzyme) profiles (p < 0.001, < 0.001, < 0.001, 0.003, 0.033 and 0.002, respectively), and required more intensive care admission. Neonates from women with severe forms of preeclampsia (eclampsia and HELLP syndrome (haemolysis, elevated liver enzymes, low platelets)) had, on average, lower birthweight (p = 0.015 and 0.048, respectively) and birth length (p = 0.021, 0.017). Neonates from eclamptic mothers had poorer APGAR (appearance, pulse, grimace, activity and respiration) scores (p = 0.006 and 0.005, respectively). Conclusion: Hypertensive disorders of pregnancy exerts adverse maternal and neonatal outcomes, particularly among eclampsia and HELLP-syndrome neonates. Various challenges remain for optimal management.